Wood Pyrolysis using Aspen plus simulation and its Industrial Application - Leštinský, Pavel (GeoScience Engineering, 2016)
Over the past decades a great deal of experimental work as been carried out on the development of Pyrolysis processes for wood and waste materials. Pyrolysis is an important phenomenon in Thermal treatment of wood and the successful modelling of pyrolysis to predict the rate of volatile evolution is central to combustion calculations. Aspects of pyrolysis are discussed with a description of how various parameters like wood composition and heating rate affect the overall reaction rate and the yield of volatiles components. Then similar model made on Aspen plus and comparison of it with experimental data is discussed further.